Does self-confidence link to motivation? A study in field hockey athletes - Sari, I.; Ekici, S.; Soyer, F.; Eskiler, E. (Journal of Human Sport & Exercise, 2015)
Previous research indicated some evidence of a positive relationship between motivation and self-efficacy beliefs/perceived competence/self-perceptions. Therefore, the relationship between self-confidence and motivation was investigated in sport context in this study. Participants of this study were 111 field hockey athletes. Sport Motivation Scale (Pelletier et al., 1995) and Self-confidence Scales (Tokinan, 2008) were used for data collection. SPSS.17 package program was used to analyse the data. Descriptive statistics techniques, t-test and Pearson`s correlation analysis were used. According to the results, self-confidence was found to be positively and significantly correlating with intrinsic motivation to know and to accomplish things, intrinsic motivation to experience stimulation, external regulation, identification, introjection, intrinsic motivation and extrinsic motivation (p<0,05). Self-confidence appeared to be negatively and significantly correlating with amotivation (p<0,05). In the light of the result it could be suggested that when athletes perceive high self- confidence and efficient self-perception and trust their abilities, their motivation to practice their sports enhances. Results were discussed in line with the relevant literature and some applications were proposed.